Lifeways in the Northern Maya Lowlands New Approaches to Archaeology in the Yucatán Peninsula - Morrison, Bethany A.; Mathews, Jennifer P. (University of Arizona Press, 2022)
The flat, dry reaches of the northern Yucatán Peninsula have been largely ignored by archaeologists drawn to the more illustrious sites of the south. This book is the first volume to focus entirely on the northern Maya lowlands, presenting a broad cross-section of current research projects in the region by both established and up-and-coming scholars. To address the heretofore unrecognized importance of the northern lowlands in Maya prehistory, the contributors cover key topics relevant to Maya studies: the environmental and historical significance of the region, the archaeology of both large and small sites, the development of agriculture, resource management, ancient politics, and long-distance interaction among sites. As a volume in the series Native Peoples of the Americas, it adds a human dimension to archaeological findings by incorporating modern ethnographic data. By exploring various social and political levels of Maya society through a broad expanse of time, Lifeways in the Northern Maya Lowlands not only reconstructs a little-known past, it also suggests the broad implications of archaeology for related studies of tourism, household economies, and ethnoarchaeology. It is a benchmark work that pointedly demonstrates the need for researchers in both north and south to ignore modern geographic boundaries in their search for new ideas to further their understanding of the ancient Maya.